Prispevek k poznavanju flore okolice Ormoža (vzhodna Slovenija) - Jogan, Jernej (Natura Sloveniae, 1999)
A contribution to the knowledge of flora in the vicinity of Ormož (Eastern Slovenia) - during the Student research camp Središče ob Dravi '97, the floristical group was mapping vascular plants in 5 quadrants of the MTB grid (240-250) species recorded per quadrant). Some of the most interserting records of plants are presented in the paper: Oenothera pynocarpa and Callitriche cophocarpa have not been recorded in Slovenia before. In addition,we found several potentially naturalized plant species (Acer negundo,Calendula officianlis, Epilobium adenocaulon and Pinus strobus), new species for the subpannonian part of Slovenia and species with imperfectly known area of distribution. We have also confirmed occurrence of several rare or endangered plant species and some of the discussed species are proposed forinclusion in the red data list (Apium repens - E, Carex strigosa - R, Centunculus minimus - E, Lythrum hyssopifolia - E, Potentilla supina - R, Rumex aquaticus - V).
Keywords: Ecosystem; flora; Goričko; Plants